Clinical presentation and treatment responses in IgM-related AL amyloidosis*. (2nd October 2015) - Sissoko, Moussa; Sanchorawala, Vaishali; Seldin, David; Sworder, Brian; Angelino, Kenneth; Broce, Mike; Berk, John; Sloan, J. Mark
Abstract: Amyloid light-chain (AL) amyloidosis is a multi-organ disease due to deposition of misfolded monoclonal immunoglobulin light chains. IgM AL amyloidosis is a rare variant, about 6% of AL amyloidosis cases, and more data are needed for treatment guidance. In IgM AL amyloidosis, the clonal cell of origin may be a plasma or lymphoplasmacytic cell, and treatments targeting each are employed. We describe presenting clinical and laboratory features of 95 patients with IgM AL amyloidosis treated at Boston University Amyloidosis Center from 1996 to 2012. The median diagnosis age was 66 years (range: 38–89) with 56% males. Organ involvement rates were: kidney (51%); heart (40%); lymph nodes (25%) and gastrointestinal tract (17%). Treatment responses were analyzed for 46 patients seen after 2003. Five treatment regimens were assigned by bone marrow pathology and patient-specific factors. Overall hematologic response rates and very good partial or complete hematologic response rates, respectively, were: high-dose melphalan/stem cell transplant (HDM/SCT) 100%;80%, Bortezomib 82%;27%, Rituximab 80%;27%, immunomodulatory agents (IMids) 75%;0%, and standard dose alkylating agents (Melphalan or cyclophosphamide) 63%;19%. Overall, 5-year survival rates were significantly higher in patients with a hematological response: 79.2 ± 8.5% versus 41 ± 14.9% in non-responders, which is more favorable than typically expected in AL amyloidosis.